Multiple Mechanisms for the Action of Chymase Inhibitors - Shinji Takai; Denan Jin; Mizuo Miyazaki (Elsevier, 2012)
Angiotensin II plays an important role in regulating blood pressure. Moreover, angiotensin II directly promotes organ damage by inducing expression of various genes, such as transforming growth factor (TGF)-β and matrix metalloproteinase (MMP)-9 precursors. Blockade of angiotensin II has been shown to not only lower blood pressure, but also to prevent cardiovascular and renal dysfunction and fibrosis. Inhibition of TGF-β and MMP-9 has also been shown to prevent cardiovascular and renal damage. A mast cell-produced enzyme, chymase, generates angiotensin II and also converts precursors of TGF-β and MMP-9 to their active forms. Chymase also strongly promotes accumulation of inflammatory cells. These multiple functions of chymase may play an important role in the development and promotion of various diseases. In fact, chymase inhibitors have been shown to prevent nonalcoholic steatohepatitis, intestinal inflammation, and adhesion formation after surgery and cardiovascular and renal damage. On the other hand, chymase inhibitors, unlike angiotensin-converting enzyme inhibitors and angiotensin II blockers, have no blood pressure-lowering effect despite blocking angiotensin II formation. Thus, chymase inhibitors may be useful for preventing damage to various organs via multiple mechanisms without lowering blood pressure. Keywords:: angiotensin II, chymase, inhibitor, matrix metalloproteianase-9, transforming growth factor-β